Human anatomy and physiology - Marieb, Elaine N. R.N., Ph.D; Hoehn, Katja M.D., Ph.D
The eleventh global edition of Human Anatomy & Physiology offers the most effective approach to learning and teaching anatomy and physiology through these hallmark features: Chapter-opening roadmaps provide an overview of the key concepts in a chapter and show they are connected to each other; Career connection videos feature health care professionals who describe how the chapter content relates to their everyday work; Summary tables help students connect information and see the big picture; Focus figures and in-line figures illustrate complex concepts and enhance visual literacy; A huge range of self-assessment questions allow students to exercise critical thinking skills and prepare for tests; Homeostatic imbalance discussions and clinical case studies help students clinically apply the concepts they have learnt; Mastering A&P offers a wide range of teaching resources for instructors and allows students to be engaged in a continuous process of learning and assessment